DISTRIBUTION OF DIFFERENT PML/RARΑ BCR ISOFORMS IN INDIAN ACUTE PROMYELOCYTIC LEUKAEMIA (APL) PATIENTS AND CLINICOHEMATOLOGICAL CORRELATION - Tathagata Chatterjee; Srishti Gupta; Ajay Sharma; Sanjeevan Sharma; Prosenjit Ganguli (Mediterranean Journal of Hematology and Infectious Diseases)
Context: